Design Analysis of 26650 and 18650 LFP Cells for High Power and Low Temperature Use Cases - Florian Wätzold; Anton Schlösser; Max Leistikow; Julia Kowal (Batteries)
This study investigates the design and geometric properties of high-power and low-temperature 18650 and 26650 lithium iron phosphate (LFP) cells. The analysis focuses on the geometry and components’ thicknesses and deriving CAD models for both cell formats. Design variations were observed, even within cells from the same manufacturer. For instance, one manufacturer’s 26650 cell was not a scaled-up version of their 18650 cell, and no equivalence was found between the designs of high-power and low-temperature cells from the same manufacturer. Thus, modifications are not purely chemistry based. The results also reveal deviations from the literature values for jelly roll component thicknesses, with anode current collectors averaging 61 µm and cathode current collectors averaging 60 µm. Coating thicknesses varied, with anode coatings averaging 32 µm and cathode coatings averaging 52 µm. These variations in current collector and coating thicknesses suggest that both high-power and low-temperature LFP cell designs differ from the typical literature values. Furthermore, a trade-off was observed between low-temperature operation with two-tab designs and high pulse capability with limited minimum operating temperatures. Additionally, smaller particle sizes in anode coatings were associated with lower impedance.